The Effect of Income, Consumption, and Religiosity on the Behavior of ‘Eating Savings’ of Muslim Society in Ambon with Financial Literacy as a Moderate - Holle, Mohammad H (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
Eating savings became a solution for people to overcome daily life when the COVID-19 pandemic hit Indonesia. This research aims to examine the influence of income, consumption, and religiosity on the behavior of 'eating savings' in the muslim community of Ambon, with financial literacy as a moderate variable. This research uses a quantitative approach. The population is all muslim people in Ambon City consisting of civil servants, BUMN employees, teachers, lecturers, TNI/Polri. The number of samples used was 60 selected using the purposive sampling technique. The data collection technique used questionnaires via google forms. This study uses the structural equation modeling method using partial least square as a material for analyzing research data. The research results from the hypothesis test showed that the variables of income, religiosity, and financial literacy do not have a positive and significant effect or H0 is rejected. While the consumption variable has a positive and significant impact on eating savings H2 is accepted. This confirms that in the Covid-19 situation, the consumption of the Muslim community of Ambon remains high. People no longer think about good financial management, the most important thing is to be able to meet the needs and desires of the community. Financial literacy does not moderate the relationship of all variables, including income, consumption, and religiosity. The cause is the existence of a simple attitude and luxurious behaviour in consuming which is a lifestyle of the Muslim community of Ambon to fulfill their needs and desires.